MEWUJUDKAN IMAN YANG HIDUP: INTEGRASI TEOLOGI KRISTEN DALAM PENDIDIKAN AGAMA KRISTEN UNTUK PEMBENTUKAN KARAKTER SISWA - Nasia Lambe'; Chelsea Ahliwati Rindi, Peransi Basongan, Agung Palimbong, Erika Ratte (ADISAM PUBLISHER, 2025)
This article discusses the importance of integrating Christian theology and pedagogy in Christian Religious Education (PAK) as an effort to shape students' characters rooted in faith in Christ. Christian education that only emphasizes cognitive aspects without a strong theological basis will lose its transformative power. Conversely, education that is theological but does not pay attention to the pedagogical context can be dogmatic and uncommunicative. Through a literature study approach, this article examines various main theological concepts such as creation, incarnation, redemption, and eschatology as the theological foundation for PAK. In addition, it also discusses the urgency of unifying the content of faith and learning strategies to produce a relevant and meaningful educational process. The main focus is directed at the formation of Christian character as the fruit of the integration of faith and learning, as well as on the various challenges faced in the context of today's education, including the flow of secularism, cultural change, and the development of digital technology. This article proposes implementation strategies such as strengthening teacher competence, developing contextual curricula, and cross-institutional collaboration (schools, churches, and families) to strengthen the role of PAK as a means of discipleship. Thus, the integration of theology in education is not only a methodological need, but a call of faith in forming a generation that is spiritually and morally resilient